Photochemical Tissue Bonding of Amnion Allograft Membranes for Peripheral Nerve Repair: A Biomechanical Analysis - King, Nicholas C.; McGuire, Kalyn R.; Bejar-Chapa, Maria; Hoftiezer, Yannick A. J.; Randolph, Mark A.; Winograd, Jonathan M. (Journal of Reconstructive Microsurgery, 2023)
Background Photochemical tissue bonding (PTB) is a technique for peripheral nerve repair in which a collagenous membrane is bonded around approximated nerve ends. Studies using PTB with cryopreserved human amnion have shown promising results in a rat sciatic nerve transection model including a more rapid and complete return of function, larger axon size, and thicker myelination than suture repair. Commercial collagen membranes, such as dehydrated amnion allograft, are readily available, offer ease of storage, and have no risk of disease transmission or tissue rejection. However, the biomechanical properties of these membranes using PTB are currently unknown in comparison to PTB of cryopreserved human amnion and suture neurorrhaphy.Methods Rat sciatic nerves (n = 10 per group) were transected and repaired using either suture neurorrhaphy or PTB with one of the following membranes: cryopreserved human amnion, monolayer human amnion allograft (crosslinked and noncrosslinked), trilayer human amnion/chorion allograft (crosslinked and noncrosslinked), or swine submucosa. Repaired nerves were subjected to mechanical testing.Results During ultimate stress testing, the repair groups that withstood the greatest strain increases were suture neurorrhaphy (69 ± 14%), PTB with crosslinked trilayer amnion (52 ± 10%), and PTB with cryopreserved human amnion (46 ± 20%), although the differences between these groups were not statistically significant. Neurorrhaphy repairs had a maximum load (0.98 ± 0.30 N) significantly greater than all other repair groups except for noncrosslinked trilayer amnion (0.51 ± 0.27 N). During fatigue testing, all samples repaired with suture, or PTBs with either crosslinked or noncrosslinked trilayer amnion were able to withstand strain increases of at least 50%.Conclusion PTB repairs with commercial noncrosslinked amnion allograft membranes can withstand physiological strain and have comparable performance to repairs with human amnion, which has demonstrated efficacy in vivo. These results indicate the need for further testing of these membranes using in vivo animal model repairs.
Keywords: nerve; photochemical tissue bonding; amnion; allograft; neurorrhaphy